2021
DOI: 10.1186/s13018-021-02611-2
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker potential of lncRNA GNAS-AS1 in osteosarcoma prognosis and effect on cellular function

Abstract: Background Osteosarcoma (OS) is a type of bone cancer that occurs in children and adolescents at a rate of 5%. The purpose of this study is to explore the lncRNA GNAS-AS1 expression profile, prognosis significance in OS, and biological effect on OS cell function. Methods One hundred eight pairs of tissues were collected, and OS cell lines were purchased. lncRNA GNAS-AS1 expression in these tissues and cells were analyzed by qRT-PCR. Clinical data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…CRNDE could promote the malignant progression of glioma by attenuating the miR-384/PIWIL4/STAT3 axis (27). GNAS-AS1 has been reported to be related to the malignant progression of osteosarcoma, breast cancer, nasopharyngeal carcinoma, and non-small cell lung cancer (28)(29)(30)(31), however, its function in glioma remains unclear. In this study, we determined that GNAS-AS1 overexpression may contribute to poor prognosis in glioma patients.…”
Section: Discussionmentioning
confidence: 99%
“…CRNDE could promote the malignant progression of glioma by attenuating the miR-384/PIWIL4/STAT3 axis (27). GNAS-AS1 has been reported to be related to the malignant progression of osteosarcoma, breast cancer, nasopharyngeal carcinoma, and non-small cell lung cancer (28)(29)(30)(31), however, its function in glioma remains unclear. In this study, we determined that GNAS-AS1 overexpression may contribute to poor prognosis in glioma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are no studies on the relationship between GNAS-AS1 and Wnt/β -catenin signaling Pathway, we have reason to believe that GNAS-AS1 can affect the process and development of IDD by regulating Wnt/β -catenin Signaling Pathway. GNAS-AS1 has also been reported as a prognostic indicator of osteosarcoma (Mi et al, 2021). MIR100HG promotes the development of triple-negative breast cancer (TNBC) by regulating the P27 gene and sponging mir-5590-3p.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the expression of lncRNA GNAS antisense (lncRNA GNAS-AS1) could significantly increase in OS cells and tissues, which were positively correlated with Enneking stage and distant metastasis. Its high expression often predicted the short overall survival time ( Mi et al, 2021 ). Through regulating miR-490-3p, lncRNA GNAS-AS1 could play a major role in cell proliferation, migration and invasion, which could be an independent prognostic predictor of OS, providing a new therapeutic strategy for OS ( Mi et al, 2021 ).…”
Section: Diagnostic Biomarkersmentioning
confidence: 99%
“…Its high expression often predicted the short overall survival time ( Mi et al, 2021 ). Through regulating miR-490-3p, lncRNA GNAS-AS1 could play a major role in cell proliferation, migration and invasion, which could be an independent prognostic predictor of OS, providing a new therapeutic strategy for OS ( Mi et al, 2021 ). The expression of circRNA-mitochondrial tRNA translation optimization 1 (circ_MTO1) in OS is low, its expression level is significantly correlated with Enneking staging, and its high expression in the tumor meant that the Enneking staging was lower in OS patients who had better neoadjuvant chemotherapy response and longer disease-free survival (DFS) ( Shi et al, 2021 ).…”
Section: Diagnostic Biomarkersmentioning
confidence: 99%